Efektivitas Penambahan Asam Cuka (CH3COOH) Dengan Dosis yang Berbeda Pada Lokan / Kijing (Pilsbryoconcha Sp.) Crispy - Oppi Anggraini (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Local kijing is one of the organisms contained in the mill stream that precisely located in Aceh Singkil. Based on observations of kijing in Aceh Singkil utilization is still not optimal due to the information and knowledge society in the processing of raw materials is still minimal. Therefore, a snack product made in the form of crispy kijing. The purpose of this study was to determine the protein and organoleptic content of crispy kijing with the addition of vinegar acid (CH3COOH) concentration 0%, 5%, 10% dan 15%. The research method is experimental laboratories. The results of testing the protein content at the vinegar concentration of 0%, 5%, 10% and 15% amounted to 26.3; 19.69; 24,63; dan 26,46. The highest content of crispy kijing protein is the addition of 15% vinegar acid concentration. Organoleptic results of crispy kijing with the addition of 0% vinegar acid concentration of 8.31 μ μ ≥ 8.63, 5% vinegar acid concentration of 8.25 μ μ ≥ 8.41, 10% vinegar acid concentration of 8 ≤ μ ≥ 8,24, and 15% vinegar acid concentration of 7.85 ≤ ≥ 8.25 so that the crispy kijing / lokan is suitable for consumption.